Technologies of Life and Death : From Cloning to Capital Punishment - Oliver, Kelly, 1958- (Book collections on Project MUSE., 2013)
The central aim of this book is to approach contemporary problems raised by technologies of life and death as ethical issues that call for a more nuanced approach than mainstream philosophy can provide. To do so, it draws on the recently published seminars of Jacques Derrida to analyze the extremes of birth and dying insofar as they are mediated by technologies of life and death. With an eye to reproductive technologies, it shows how a deconstructive approach can change the very terms of contemporary debates over technologies of life and death, from cloning to surrogate motherhood to capital p.